Plantar Pressure Changes of Patients with Heel Valgus in Rheumatoid Arthritis - Nurettin Tastekin,; Hakan Tuna,; Murat Birtane,; Kaan Uzunca, (Archives of Rheumatology, 2009)
Objective: Long-standing rheumatoid arthritis (RA) causes foot problems in approximately 90% of the patients. In this study, we aimed to document the plantar pressure distribution changes in RA patients with heel valgus and to compare results in those without valgus. Material and Methods: This study was performed on 22 feet of 11 RA patients with bilateral heel valgus (Group 1) and 28 feet of 14 RA patients without heel valgus deformity (Group 2). Both static and dynamic pedobarographic evaluations were performed in both groups to determine the plantar pressure values and to make comparisons between the groups. Erosion scores of both groups were also compared. Results: In dynamic pedobarographic evaluation, only the plantar contact area was found to be greater in Group 1 than Group 2. However, in the static evaluation, forefoot pressure percentage, plantar contact area and forefoot plantar contact area values were higher in Group 1 than Group 2. In radiographic evaluation, erosion scores were again found to be higher in Group 1. Conclusion: According to results of the pedobarographic evaluation in this study, heel valgus deformity in the RA patients led to increases in plantar contact area and forefoot pressure percentages. (Turk J Rheumatol 2009; 24: 67-71)